2024
DOI: 10.3390/ijms25031840
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Sideritis scardica and Clinopodium vulgare Alleviate Cognitive Impairments in Scopolamine-Induced Rat Dementia

Maria Lazarova,
Elina Tsvetanova,
Almira Georgieva
et al.

Abstract: Sideritis scardica Griseb. and Clinopodium vulgare L., belonging to the Lamiaceae family, are rich in terpenoids and phenolics and exhibit various pharmacological effects, including antioxidant, anti-inflammatory and anti-cancer activities. While the memory-enhancing impacts of S. scardica are well documented, the cognitive benefits of C. vulgare remain unexplored. This study assessed the potential effect of C. vulgare on learning and memory in healthy and scopolamine (Sco)-induced memory-impaired male Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 113 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…Analysis revealed that, as expected, Sco suppressed hippocampal and cortical pCREB/BDNF protein expression, leading to memory impairment in rats. This aligns with literature data and findings from our previous research [ 22 , 25 , 97 ]. Treatment with M. vulgare significantly increased pCREB expression in the cortex of the animals with dementia.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Analysis revealed that, as expected, Sco suppressed hippocampal and cortical pCREB/BDNF protein expression, leading to memory impairment in rats. This aligns with literature data and findings from our previous research [ 22 , 25 , 97 ]. Treatment with M. vulgare significantly increased pCREB expression in the cortex of the animals with dementia.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that the LC is activated in response to novelty [ 87 ] and arousal [ 88 ], and its degeneration is a hallmark of AD [ 89 ]. Sco treatment has been shown to depress the monoaminergic systems in the cortex and hippocampus, a finding corroborated by our previous research [ 22 , 25 , 64 ]. Treatment with M. vulgare has been observed to positively affect the NA system but did not significantly impact the Sero system.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations